Precarity, the future of architectural research in a time of much uncertainty - Trubiano, Franca (Enquiry The ARCC Journal for Architectural Research, 2023)
Editoral framing of the special issue of ENQ on PRECARITY: PhD conference on architectural research at the limits of technology, project-making, and history/theory held on APRIL 22-23, 2022 and organized and sponsored by the PhD Program in Architecture at UPENN, Weitzman School of Design